2000
DOI: 10.1007/s004010051179
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A-associated fatal central nervous system angiopathy in a bone marrow transplant recipient: an autopsy case

Abstract: We report here the case of a 32-year-old woman who suffered from a unique angiopathy in the central nervous system (CNS). She died of multiple infarcts in the brain stem and cerebellum during treatment with cyclosporine A after bone marrow transplantation for refractory anemia with excess of blasts. The autopsy findings showed segmental narrowing of the basilar artery, in which circumferential dissection of the internal elastic lamina had occurred. The distal portion of the basilar artery was obstructed by upw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…Histopathologic evidence of acute and chronic vessel injury has been described in postmortem studies, including intimal thickening, segmental vessel narrowing, intimal dissection, and organized thrombi. 28 This supports a pathologic process similar to that of TMA. Minute hemorrhages as well as focal hematoma and sulcal hemorrhage can be seen with PRES.…”
Section: Discussionsupporting
confidence: 63%
“…Histopathologic evidence of acute and chronic vessel injury has been described in postmortem studies, including intimal thickening, segmental vessel narrowing, intimal dissection, and organized thrombi. 28 This supports a pathologic process similar to that of TMA. Minute hemorrhages as well as focal hematoma and sulcal hemorrhage can be seen with PRES.…”
Section: Discussionsupporting
confidence: 63%
“…91 Endothelial injury, including cerebral arterial dissection, was observed in autopsy studies of patients with cyclosporine toxicity. 92 Endothelial injuries in association with activation of cell adhesion molecules and cytokines have been implicated in eclampsia, infection, transplantation, and perhaps other conditions. 68 A damaged endothelium in the cerebral arteries may lead to an impaired autoregulation and, hence, lower the blood pressure threshold for autoregulatory breakthrough.…”
Section: Pres Pathogenesis and Mechanismmentioning
confidence: 99%
“…Furthermore, it was shown to cause direct toxic damage to brain cells, particularly to oligodendrocytes and neurons (McDonald et al 1996), as well as mild cerebral cell loss (Nassbaum et al 1995). Several fatal cyclosporin A-associated deaths have been presented in the literature (Nassbaum et al 1995;de Perrot et al 2000;Koide et al 2000), one of them in a medico-legal setting after accidental administration of the drug in a 10-fold concentration via a central line: the patient subsequently developed a massive cerebral oedema with brainstem compression resulting in death (de Perrot et al 2000). The non-accidental cases were also characterised by substantial cerebral oedema resulting in brain stem compression (Nassbaum et al 1995;Koide et al 2000), of which the more recent case showed a unique angiopathy with segmental narrowing of the basilar artery with intimal dissection resulting in multiple necrotic CNS lesions (Koide et al 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Administration of cyclosporin A is known to be associated with a wide range of systemic complications: neurotoxicity is noted in approximately 20% of patients and symptoms such as tremors, paraesthesias, headaches, confusion, seizures and coma have been recorded (Koide et al 2000). The cyclosporin A encephalopathy is usually associated with white matter hypoattenuation on cranial CT scans, but is generally reversible after discontinuation of the drug (Hughes 1990).…”
Section: Discussionmentioning
confidence: 98%